2019
DOI: 10.1557/adv.2019.365
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Novel Ceramic Tool Performance in the Machining of Ti-6Al-7Nb Alloys

Abstract: Considering their distinctive properties, titanium alloys are used in foremost industries, including the aeronautic, automotive and biomedical industries. The reduced machinability of titanium alloys is due to their low thermal conductivity and high plasticity behavior. In the biomedical sector, one of the most studied alloys is Ti-6Al-4V. In the case of the Ti-6Al-7Nb alloy, scarce investigations are identified, related to machinability studies. The machining of Ti-6Al-7Nb alloy requires the development of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Based on the literature review, the MQL method used in this study was conducted with a vegetable-based cutting oil with a thermal conductivity of 0.5-1 W/m.K [18]. In contrast, graphene is produced from synthetic graphite powder [19] and graphene nanoparticles can exhibit an impressive thermal conductivity of up to 3000-5500 W/m.K [20,21]. Consequently, graphene added nanofluid based MQL (NMQL) is improve heat transfer.…”
Section: Cutting Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature review, the MQL method used in this study was conducted with a vegetable-based cutting oil with a thermal conductivity of 0.5-1 W/m.K [18]. In contrast, graphene is produced from synthetic graphite powder [19] and graphene nanoparticles can exhibit an impressive thermal conductivity of up to 3000-5500 W/m.K [20,21]. Consequently, graphene added nanofluid based MQL (NMQL) is improve heat transfer.…”
Section: Cutting Temperaturementioning
confidence: 99%
“…These properties lead to rapid tool wear and plastic deformation of cutting tools reported by researchers [17,18]. For instance, Risco-Alfonso et al [19] conducted turning exper-iments on Ti-6Al-7Nb alloy using ceramic tools under dry cutting conditions. Their results showed that at the cutting speed of 200 m/min, the tool life was limited to only 6 minutes.…”
Section: Introductionmentioning
confidence: 99%